Inside Fatima ; Breaking up is hard to do ; Sakay the movie [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Exposes the alledged irregularities of Fatima administration through silhoutte interview with students. Deals with legal annulments & marital break-ups. The making of Sakay, the movie with Raymond Red as film director.